THE DETERMINATION OF THE KIND OF PHASE-TO-PHASE SHORT CIRCUIT IN CURRENT LINE PROTECTION OF 6–35 KV - F. A. Romaniuk; O. A. Huryanchyk; M. A. Shevaldin; V. S. Kachenya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The methods of determining the kind of phase-to-phase short circuit (SC) on the lines of 6–35 kV for improvement the technical perfection of their current protections are surveyed. Preference is given to the method of determining damages according to the relative unbalance the operating currents. The possibility of using the phase currents or their differences for this purpose is demonstrated. The method of computational experiment was used to investigate the influence of the DC load line and transition resistance at the failure site on the relative asymmetry of the currents that ultimately determines the reliability of the establishment of the kind of SC. It is discovered that when the phase currents are used to determine the type of the failure higher sensitivity to remote two-phase SC is achieved. However, in this case, the accuracy of determining the type of failure is more affected by currents of the line load. Determination of failure with the use of differences of phase currents is less sensitive to remote two-phase SC. However, this provides less impact on the accuracy of determining the type of failure of load line currents. Transition resistance at the failure site shifts the relative unbalance of the currents to the area of twophase SC. It is established that despite the kind of a remote SC in parallel lines the proposed methods provide accurate determination of types of failure that simultaneously occurs on the monitored line. When failures are superpositioned, one of which is on one of the parallel lines near the common bus and the other second on the monitored bus, the kind of the SC, determined by any of the proposed methods may differ from the actual one. It depends on the types of resulting failures, the combinations of shutting phases, the steady-state current distribution in the network and other factors. The proposed methods make it possible to determine the kind of phase-to-phase SC, in the worst case, for a time not exceeding the period of industrial frequency.